Intravenous Infusion of Magnesium Sulphate During Subarachnoid Anaesthesia in Hip Surgery and Its Effect on Postoperative Analgesia: Our Experience - Pastore, A (Università di Salerno, 2013)
The treatment of degenerative hip joint disease involves modern operative techniques and the use of prosthetic devices individualized on each patient. Being a surgery of considerable importance, great attention is always given by the anaesthesiologist to postoperative analgesia. In general, our goal is to limit the doses of NSAIDs, known to be associated with haemostasis interference and alteration of gastrointestinal apparatus; component of our baseline analgesic protocols after arthroplasty is morphine given parenterally. In order to steadily improve analgesic techniques, which directly impact on patient outcome, we experimented the use of a continuous infusion of magnesium sulphate during subarachnoid anaesthesia. Magnesium sulphate is the drug of choice in case of eclampsia, and pre-eclampsia (for the risk of evolution in eclampsia). According to the most recent findings, this drug has also analgesic properties: its use as an adjunct to analgesia is based on a non-competitive antagonism towards the NMDA receptor and on the blocking of calcium channels: these properties prevent the mechanisms of central sensitization due to nociceptive stimulation of peripheral nerves.